Separation of oil and water using sugarcane bagasse - Noor Atikah, Mohd Badruddin (2012)
Sugarcane bagasse is one of the agricultural residues from sugar making industry.The usage of this organic waste has not been widely discovered here in Malaysia.In Malaysia sugar industry,estimated one tons of sugarcane generates 280 kg of bagasse.Sugarcane bagasse is a very good fibrous organic waste beside have a very high content of carbon. This research will be investigate the effectiveness of sugarcane bagasse as a material to adsorp oil and water. Other than that,the study is to increase the usage of sugarcane bagasse and reduce the number of organic waste produce by the industry.Raw bagasse and bagasse that is modified using sulphuric acid is used to determined the effectiveness of sugarcane bagasse as material to separate oil,which is in this research,crude palm oil is used.The research are done with different weight of bagasse for each bagasse sample and different size of bagasse.As a result, sugarcane bagasse can adsorp oil from the oil sample because of the high carbon content and adsorption is one of method for separation.The particle size are one of the factors effecting the adsorption capacity.The smaller particle size have greater surface area have higher adsorption capacity. Raw bagasse can adsorp more compare to that is modified using sulphuric acid.Chemical modification by using only sulphuric acid is not signifacantly increasing the adsorption capacity of the bagasse.Sugarcane bagasse can be one of the material to separate oil and water as an alternative method of separation.This alternative method can be used as one of the method to separate oil from water for cleaning the waste oil from oil spills as well as a method to separate oil from palm oil industrial waste.